An investigation into students’ attitudes towards improvisation of instructional materials in Basic Science and Technology in Lagos State Schools - Raheem, Isiaka Ayobi; Raheem-Folayinka , Ganiyat Pelumi; Abdukarim , Abdulsalam; Kayode , Ufomanefe; Adedayo, Afolabi (Journal of Education For Sustainable Innovation, 2025)
This study examined students’ attitudes toward the use of improvised instructional materials in Basic Science and Technology. A quasi-experimental design, complemented by a descriptive survey, was employed to assess the attitudes of students exposed to an improvised alternating current generator (IACG) during instruction compared to those who received conventional teaching. A total of 360 Basic 9 students were randomly selected from six public junior secondary schools across Lagos State. Research instruments included the IACG, a lesson plan, and a structured questionnaire. These instruments were validated and pilot tested, with the questionnaire yielding a reliability coefficient of 0.88 using Cronbach’s Alpha. Findings revealed a statistically significant difference in attitudes between the experimental and control groups, indicating a more favorable disposition toward improvisation among students taught with the IACG. Based on these findings, it is recommended that schools regularly integrate improvised instructional materials into science teaching. Furthermore, both schools and families should encourage students to engage in improvisation activities to enhance practical understanding and innovation in science education across Lagos State and beyond.